2008
DOI: 10.1002/anie.200802223
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of an Aspartate‐Based Epoxidation Catalyst with Amide‐to‐Alkene Peptidomimetic Catalyst Analogues

Abstract: Keywordsepoxidation; peptide; asymmetric catalysis; olefin isostere; fluorine; peptidomimetic The biosynthesis of natural products that contain epoxides represents a powerful stimulus for the study of "epoxidase" enzymes. [i] Likewise, these processes have inspired a generation of science focused on small molecule catalysts that mediate selective epoxidations through a variety of mechanisms. [ii] With respect to the naturally occurring epoxidases, the mechanistic basis of O-atom transfer is often associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
70
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 122 publications
(74 citation statements)
references
References 53 publications
(33 reference statements)
2
70
0
2
Order By: Relevance
“…8d As shown in Scheme 1, we found a peptide-based catalyst 6 that is highly selective in forming the 2,3-epoxide of farnesol ( 8 ) over the 6,7-epoxide ( 9 ) or the 10,11-epoxide ( 10 ) with 1:1:>100 site selectivity ( 10:9:8 ) and 86% ee in forming 8 . In addition, we found another catalyst ( 7 ) that exhibits highly unique site selectivity for the 6,7-position (1:8:1, 10:9:8 ) of farnesol, albeit with low enantioselectivity (10% ee).…”
Section: Introductionmentioning
confidence: 79%
See 4 more Smart Citations
“…8d As shown in Scheme 1, we found a peptide-based catalyst 6 that is highly selective in forming the 2,3-epoxide of farnesol ( 8 ) over the 6,7-epoxide ( 9 ) or the 10,11-epoxide ( 10 ) with 1:1:>100 site selectivity ( 10:9:8 ) and 86% ee in forming 8 . In addition, we found another catalyst ( 7 ) that exhibits highly unique site selectivity for the 6,7-position (1:8:1, 10:9:8 ) of farnesol, albeit with low enantioselectivity (10% ee).…”
Section: Introductionmentioning
confidence: 79%
“…Previously reported results for prenol and nerol, which were epoxidized using previously reported conditions (a), indicated that ( Z )-olefins were best suited for the system. 8d Epoxynerol ( 11 ) can be synthesized with 93% ee and 79% yield and epoxyprenol ( 12 ) is formed in 92% ee and 75% gas chromatography (GC) yield (Table 1, entries 1 and 2, respectively). The optimal pattern for the substitution, in terms of steric bulk of substituents, remained an intriguing avenue for investigation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations